Cytokine release syndrome caused by immune checkpoint inhibitors: a case report and literature review - Xiuping Zhang; Yang You; Pengfei Zhang; Yan Wang; Feng Shen (Future Science OA)
Immune checkpoint inhibitors (ICIs) have gained widespread application in the treatment of malignant tumors. Cytokine release syndrome (CRS) is a systemic inflammatory response triggered by various factors, including infections and immunotherapy. We present a case of CRS occurring in a gastric cancer patient after receiving combination therapy of tislelizumab, anlotinib and combination of capecitabine and oxaliplatin. Nineteen days after the third dose of tislelizumab, the patient experienced sudden unconsciousness, frothing at the mouth, convulsions and other clinical manifestations resembling epileptiform seizures. Elevated inflammatory markers, cytokine levels and ferritin were markedly increased. Given the absence of definite clinical evidence for metastasis and infection, the diagnosis of CRS was considered. Subsequent management with glucocorticoids and intravenous immunoglobulin resulted in the patient’s improvement. However, antitumor therapy was halted, ultimately leading to death. The administration of ICIs can incite CRS, a severe, rapidly progressing condition with a poor prognosis, demanding clinical attention. Cytokines play a dual role in the pathophysiology of immune-related adverse events by mediating self-tolerance attenuation and enhancing the activation of cytotoxic T cells in the antitumor process of ICIs. The therapy of glucocorticoids combined with cytokine inhibitors may become an effective remedy.